A systematic review of school-based interventions targeting social communication behaviors for students with autism. (February 2019) - Sutton, Bronwyn M; Webster, Amanda A; Westerveld, Marleen F
Initiating and responding to peers are social communication behaviors which are challenging for students with autism. We reviewed intervention studies set in mainstream elementary schools, which targeted these behaviors and reported on intervention outcomes as well as the resources required for their implementation. A total of 22 studies met the criteria for inclusion. Findings suggest that school-based interventions can increase the frequency and duration of initiating and responding behaviors in elementary school aged students with autism. These interventions were resource-intensive and usually delivered by researchers or teaching assistants away from the classroom. Future research should build on this emerging evidence base to consider interventions which could be implemented by classroom teachers as part of the classroom program.